Can cognitive science help us understand quantum theory? - Realpe-Gómez, John [UNESP] (2019)
ICTP South American Institute for Fundamental Research Instituto de Física Teórica Universidade Estadual Paulista, Rua Dr. Bento T. Ferraz 271